A história e o acervo da Tuna Luso brasileira: troféus que contam a trajetória de um clube centenário - JUNIOR SILVA, Bernadino da Costa e (2019)
One of the most traditional clubs in the north of the country , the Tuna Luso Brasileira, owned a large collection of trophies marking the history of the club during its over one hundred year history. But the club suffers from the same reality that affects most of the Brazilian sports clubs, the lack of records of your holdings, in others words, catalog, conserve and preserve are not priorities in the activities of the boards governing clubs. Therefore, through the access granted by the board of directors, this work started a enrollment process of the trophy collection of Tuna Luso Brasileira and analyze their conservation status so that with this data the club, the board and its fans can have access to information on part of its collection of trophies and that with this record can initiate the process of building the Museum of Tuna Luso Brasileira.